Socialization of Islamic Values Related to Environment Preservation at Misykat Al-Anwar Pesantren in Bogor - Rizaldi Parani; Eva Elitanisha Mirelya Angeline Hia; Herman Purba (LONTAR: Jurnal Ilmu Komunikasi, 2024)
Pesantrens (Islamic boarding schools) have followed changes in the society and experienced modernization. This is demonstrated by the emergence of pesantrens in Indonesia that are moved to link education based on Islamic values with environmental issues. This research intends to discuss the role of pesantren as religious institutions as well as education in building awareness of the environment. The approach used in this research is qualitative with the phenomenological method. Data in this research were obtained through semi-structured interviews and field observations which were then analyzed through coding. The results of this research show that there is a strong connection between verses in the Koran and environmental conservation. Apart from that, pesantren leader has an important role in formulating the basic values that become the organizational culture. Communication built between pesantren owner, teachers and students is fundamental in socializing organizational values. The process of conveying messages carried out by the Misykat Al-Anwar Pesantren to its students is carried out through several stages, namely anticipatory socialization, encounter socialization, and metamorphosis socialization. These stages also show that the socialization process carried out at the Misykat Al-Anwar Pesantren regarding the integration of Islamic values in building awareness of the environment is highly useful.